Brand awareness and its relationship with theme branding and brand association of Sunway Pyramid - 389862 Lee, Mei Chern; Noraini Abu Talib, supervisor; Fakulti Pengurusan dan Pembangunan Sumber Manusia (2009)
Project Paper (Sarjana Muda (Pengurusan - Pemasaran)) - Universiti Teknologi Malaysia, 2009